The Woods - Coben, Harlan (New York : Signet Books, 2007)
Twenty years ago, four teenagers at summer camp walked into the woods at night. Two were found murdered, and the others were never seen again. Four families had their lives changed forever. Now, two decades later, they are about to change again. For county prosecutor Paul Copeland, mourning the loss of his sister has only recently begun to subside. Balancing family life and a rapidly ascending career distracts him from his past traumas, but only for so long. When a homicide victim is found with evidence linking him to Cope, the well-buried family secrets are threatened. Is this victim one of the campers who disappeared with his sister? Could his sister be alive? Cope has to confront so much he left behind that summer--he must decide what is better left hidden in the dark and what truths can be brought to the light.
Keywords: Missing children -- Fiction; Suspense fiction